2006
DOI: 10.1016/j.febslet.2006.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Noise‐reduction filtering for accurate detection of replication termini in bacterial genomes

Abstract: Bacterial chromosomes are highly polarized in their nucleotide composition through mutational selection related to replication. Using compositional skews such as the GC skew, replication origin and terminus can be predicted in silico by observing the shift points. However, the genome sequence is affected by myriad functional requirements and selection on numerous subgenomic features, and elimination of this ''noise'' should lead to better predictions. Here, we present a noise-reduction approach that uses low-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The power spectrum PS ( k ) of F ( k ) was further defined as PSfalse(kfalse)=|Ffalse(kfalse)|2,k=0,1,2,,N1at each frequency k . In this power spectrum, GC skew shows the greatest contributing component at 1-Hz frequency, corresponding to the two replichores shifting between two regions of opposite polarity as in a sine curve (Arakawa et al 2007). The Math:FFT module of Perl (http://search.cpan.org/~rkobes/Math-FFT-1.28/FFT.pm) was used for FFT calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The power spectrum PS ( k ) of F ( k ) was further defined as PSfalse(kfalse)=|Ffalse(kfalse)|2,k=0,1,2,,N1at each frequency k . In this power spectrum, GC skew shows the greatest contributing component at 1-Hz frequency, corresponding to the two replichores shifting between two regions of opposite polarity as in a sine curve (Arakawa et al 2007). The Math:FFT module of Perl (http://search.cpan.org/~rkobes/Math-FFT-1.28/FFT.pm) was used for FFT calculation.…”
Section: Methodsmentioning
confidence: 99%
“…By using the available sequence information it was observed that the change in the GC skew points towards the dif chromosome dimer resolution site as the main fork fusion site, rather than any of the ter sites [52,53,54,55]. Differences in the types and rates of single base mutations in the leading and the lagging strand are thought to result in asymmetric replication-related mutation pressures, leading to the accumulation of G over C in the leading strand [55,56,57].…”
Section: The Location Of Fork Fusion Eventsmentioning
confidence: 99%
“…In eubacteria, the replication-related strand asymmetry results in two replichores of nearly equal lengths (note that replichores are not exactly symmetrical in many bacteria, especially in the phylum Firmicutes) but with opposite polarity. GC skew graphs in these species therefore resemble the graph of a discrete sine curve, a graph composed of Y = -1 for t 0 ~ (t 1 - t 0 )/2 and Y = 1 for (t 1 - t 0 )/2 ~ t 1 , and this “shape” of the GC skew graph can be assessed by observing the strength of the 1 Hz signal of its Fourier transformation [68]. Fourier transformation mathematically decomposes a given signal into a set of constituent frequencies, and the most simple frequency component of 1 Hz corresponds to a sine curve spanning all across the given signal duration.…”
Section: Measures Of Strand Biasmentioning
confidence: 99%
“…Numerous methods have been proposed for the analysis of compositional asymmetries, including multivariate statistics [31, 67] and signal processing methods based on Fourier [68] and wavelet transformations [50, 69] and wavelet-based multifractal analysis [70] (see [61] for comprehensive review). The key to these analyses is the quantitative measurement of the strength of strand bias.…”
Section: Introductionmentioning
confidence: 99%